Vascular perfusion, body composition and muscle strength in chronic kidney disease patients on regular hemodialysis program - Bernardino, Bruna (2015)
Hemodialysis is a technique that effectively replaces some functions of the human kidney, allowing the survival of such patients, since loss of kidney function is incompatible with life. In most patients with chronic kidney disease, the level of renal function tends to gradually decrease over time. The most serious outcome of chronic kidney disease is renal failure. The vascular access is vital in patients with chronic renal failure undergoing dialysis and their dysfunction is a major cause of morbidity and hospitalization. Adequate vascular access for hemodialysis defines not only a better therapeutic outcome and patient survival. The flow of arteriovenous fistula (AVF) is an important factor in the successful execution of the hemodialysis. Were studied 27 patients, 20 males and 7 females, with ages between 39 and 94 years old. The diameter and the flow of the draining vein were evaluated by ultrasound flow. Were also carried out the Hand Grip Test, the Pinch Gauge Test and it was done an anthropometric evaluation using a bioimpedance scale. This study aimed to identify the relationship between vascular perfusion, body composition and muscle strength in chronic kidney disease patients on regular hemodialysis program. The average flow of the arteriovenous fistula was 1340.096±304.615ml/min and the diameter of the arteriovenous fistula was, on average, 0.57±0.06mm. To check for significant differences between the variables we used the Spearman correlation coefficient test. When correlated left handgrip strength and average flow (r = -0.576, p = 0.01), pinch gauge test of the opposite side of the fistula and average flow (r = -0.450, p = 0.059) and visceral fat and average flow (r = -0.444, p = 0.05), there were statistically significant negative correlations. Individuals with higher results in the pinch gauge test in left finger showed lower flow, lower diameter and lower area of the draining vein. Taking into account the results obtained, we can see that the sample is relatively small, which means that the conclusions of this study are not extrapolated to the Portuguese population in regular hemodialysis program, but just be confined to the group of patients evaluated. The results suggest that there is a negative relationship between the flow of the arteriovenous fistula and muscle strength and body composition. For higher values of muscle strength correspond lower flow values of the draining vein.